The new cosmology : (World Scientific, 2005)
This volume presents a comprehensive introduction to modern cosmology from an astrophysical viewpoint. Key features of the book are: breadth of topics covered, from quantum cosmology to recent observational advances; up-to-the-minute inclusion of many recent results, e.g. from the WMAP satellite; the level of the work, suited to both students and professionals in the field.